NILAI-NILAI SUFISME DALAM JAMAAH SHALAWAT WAHIDIYYAH DI KEDIRI DAN MALANG - Wahab, Fatkhul (LP3M IAI Al-Qolam, 2017)
Among Muslim communities, love of the Prophet Muhammad embodied in a religious tradition known as shalawÃÂh tradition. ShalawÃÂh is an expression of deep gratitude for the guidance to Muslims on the right path. Sufism that emphasizes reading ShalawÃÂh of the Prophet Muhammad as dhikr primarily is ShalawÃÂh WÃÂhidiyah. The main purpose of ShalawÃÂh WÃÂhidiyah is to alleviate people from the shirk and return to the straight and true that by pleasing Allah. The focuses of this study are: (1) how do the precepts and values of Sufism in the Jamaat ShalawÃÂh WÃÂhidiyah? (2)  How do the precepts and values are promoted and practiced by Jamaat ShalawÃÂh WÃÂhidiyah? (3)  How does the experience of spirituality Jamaat ShalawÃÂh WÃÂhidiyah? This study is a qualitative study by using a naturalistic paradigm and phenomenology approach. The data were collected by in-depth interviews, participant observation, and documentary in the form of journals, magazines and so on. While the data analysis techniques include data reduction, presentation of data, the validity of the data and drawing conclusions. The results of this study indicate that: (1) ShalawÃÂh WÃÂhidiyah precepts include: a. li AllÃÂh, bi AllÃÂh; b. li al-RasÃ Â«l, bi al-RasÃ Â«l; c. li al-ghauts bi al-ghauts; d. yuthÃÂ« kull dzÃÂ« Ã¡Â¸Â¥aqq; e. taqdÃÂ«m al-hamm tsumm al-hamm, fa al-faÃ¢â¬â¢ tsumm al-fa. The values contained in ShalawÃÂh WÃÂhidiyah Sufism, among others: taubah, ikhlÃÂsh, syukr, mahabbah. (2) Socialization ShalawÃÂh WÃÂhidiyah precepts are done by 1. individual, 2. packaged in a formal form as mujÃÂhadah nishf al-sanah and mujÃÂhadah kubrÃÂ, 3. through dreams, 4. implemented in the form of books, magazines, newsletters, and CDs. While this practice ShalawÃÂh WÃÂhidiyah carried out in different ways mujÃÂhadah usbÃ Â«iyyah, mujÃÂhadah syahriyyah, mujÃÂhadah rubÃ¢â¬â¢ al-sanah, mujÃÂhadah nishf al-sanah, and so forth. Keywords: The values of Sufism, ShalawÃÂh WÃÂhidiyah